1996
DOI: 10.1080/11250009609356116
|View full text |Cite
|
Sign up to set email alerts
|

The crested newt (Triturus carnifex) in the Submediterranean: Reproductive biology, body size, and age

Abstract: The annual reproductive cycle of both sexes of Triturus carnifex from the Submediterranean was analysed, as well as complex relationships between fecundity, body size, and age. Highly significant seasonal variations in snout-vent length-adjusted gonads, fat bodies, and liver weight were found in both sexes. Variations in cycle due to geographic location and climate were recorded. Newts exhibited extended residence in water and lengthening of breeding period. Body size was significantly correlated with age in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…Similarly, Verrell and Francillon (1986) and Cvetković et al (1996) reported that age was significantly correlated with SVL, but only in males of T. vulgaris and T. carnifex. Also, Marunouchi et al (2000) found significant correlations between SVL and age in six populations for both sexes in Cynops pyrrhogaster and they reported a significant correlation for only males in three populations and for only females in two populations.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, Verrell and Francillon (1986) and Cvetković et al (1996) reported that age was significantly correlated with SVL, but only in males of T. vulgaris and T. carnifex. Also, Marunouchi et al (2000) found significant correlations between SVL and age in six populations for both sexes in Cynops pyrrhogaster and they reported a significant correlation for only males in three populations and for only females in two populations.…”
Section: Discussionmentioning
confidence: 84%
“…In crested newts, large females have more oocytes and heavier ovaries, i.e. they have higher fecundity than smaller females (Cvetković et al. , 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In crested newts, large females have more oocytes and heavier ovaries, i.e. they have higher fecundity than smaller females (Cvetković et al, 1996). This suggests that the increased sexual dimorphism can be related to an increase of parental investment (more eggs, larger eggs or both).…”
Section: Discussionmentioning
confidence: 99%
“…5. Results for the Vlasi populations were compared with data from the literature (Cvetković et al, 1996and A. Ivanović, unpublished data on T. macedonicus and Üzüm, 2006and Üzüm and Olgun, 2009 on T. ivanbureschi). In three out of four populations females are larger than males of the same age.…”
Section: Resultsmentioning
confidence: 99%